Nurses’ Knowledge Regarding Anthropometry Measurement and Clinical Assessment for Patient Undergoing Hemodialysis - Azhar Hamza Gaber, Ibrahim A. Ai-Ashour, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To Assess of nurses’ knowledge regarding anthropometry measurement and clinical assessment. And to find out relationship between nurses’ knowledge and their demographic data. Methodology: A descriptive study was carried out in order to achieve the stated objective, The study starting from March 2ed ,2022 until the April 1st,2022.The study was conducted in AL-Najaf AL-Ashraf Hospital,in Hemodialysis Centers of Al-Sadder Medical City; Al-Hakeem General Hospital and Al-Najaf-Teaching-Hospital. Non probability (purposive) sample was selected (80) of nurses those who work in Hemodialysis Centers. The sample have been selected according to the following criteria(Both gender of nurses, All level of education. Nurse work in Hemodialysis Centers at least 6month). A Questionnaire was designed and constructed by researcher to assess the nurses’ knowledge regarding anthropometry measurement and clinical assessment. the questionnaire was prepared and constructed of two parts, PartI: Demographic Data: wich composed of (6) items which include age, gender, level of education, years of experience, participate in training course related to nutritional status assessment, developed self independently and PartII: Nurse’s Knowledge regarding A-Anthropometry measurement which consist from (25) items, which include questions about how to measurement and calculate weight, hight, Body mass index, skin fold thickness, Mid upper arm circumference and Waist \Hip Ratio, And C-Clinical assessment which consist from (15) items, which include questions about clinical manifestation related to normal and abnormal nutritional status assessment. Data was analyzed by using of descriptive data analysis (frequencies, percentages, mean, standard deviation, and graphical presentation) and by using of inferential analysis, ANOVA test). Results: According to the study's findings, the majority of the study sample had poor knowledge of anthropometry measurement and clinical assessment. Additionally, there was a highly significant difference between nurses' knowledge and their age group and years of experience at a p-value of less than 0.05. Additionally, there are no significant differences in nurses' knowledge based on their gender, level of education, participation in training courses, or develop themselves independently. According to the study's findings, (36.3%) of the population is between the ages of 26 and 30. The study sample reveals that women make up 62.5 percent of the sample gender, while men make up 37.5%. About (38.8%)% and (35%)% of the study sample's participants, respectively, had nursing institute qualifications. Conclusions: According to the study's findings, nurses who work in hemodialysis centers had poor scores on both the clinical assessment knowledge test and the anthropometry measurement test. Additionally, a large percentage of nurses who work in hemodialysis centers revealed poor staff nurses knowledge on nutritional status assessment.. Recommendation: They need to be prepared for the educational program for nurses working in hemodialysis centers, particularly the nutritional status assessment for hemodialysis patients educational program, which concentrated on how to perform the anthropometry measurement procedure and how to distinguish between the signs and symptoms of malnutrition patients for all new and experienced nurses working in hemodialysis centers. Additionally, hospital policies should serve as a standardized instrument for periodic evaluations of nurses' knowledge of and attitudes toward nutritional status assessment practice in hemodialysis centers.